Hyperactivity Disorders: An Assessment of Kindergarten Teachers' Knowledge: Gangguan Hiperaktif: Penilaian Pengetahuan Guru Taman Kanak-kanak - Mutashar, Mohammed Kadhim; Awad, Kadhim Jawad; Atiyah, Maher Abdulameer (Indonesian Journal on Health Science and Medicine, 2024)
Background: The symptoms of hyperactivity disorder include unpredictable, involuntary, and inappropriate movements that occur due to organic or psychological factors, as well as attention deficit disorder. Hyperactivity disorder is characterised by physical movements that surpass the normal or acceptable limit. Objective: The aim of the present study is to assess the kindergartens teachers knowledge regarding hyperactivity disorders in children. Methods: This cross-sectional study was carried out at Basrah kindergartens between November 2022 and the start of April 2023. A questionnaire was used to gather data for this study, which involved 60 sample (female) kindergarten instructors. The results were then statistically examined. Results: Sixty percent of the participants in this research were between the ages of 20 and 29. 43.3% possess a diploma in education. Of the participants, 81.7% had not undergone any training courses on hyperactivity condition, and 63.3% have 1–5 years of experience. Conclusion: The study concluded that teachers have adequate knowledge about hyperactivity disorder. Highlights: Hyperactivity disorder causes excessive, involuntary, and inappropriate movements. Assess kindergarten teachers’ knowledge of hyperactivity disorder. Teachers show adequate knowledge, but training is limited. Keywords: Kindergartens, Hyperactivity, Knowledge. Disorder, Teacher, Assessment